Environment, energy and applied technology - International Conference on Frontier of Energy and Environment Engineering (2014 : Taiwan); Sung, Wen-Pei, editor; Kao, Jimmy C. M. (Jimmy Chih-Ming), 1963- editor (London : CRC Press, 2015)
Includes bibliographical references and index